An Integrative Perspective on the Management of Knee Osteoarthritis: A Comprehensive Review (Advancements in Homeopathic Research, 2026)
Knee osteoarthritis (OA) is a chronic, progressive, degenerative joint disorder and a major cause of pain, disability, and reduced quality of life among adults and the elderly. While conventional management primarily focuses on symptom relief, there is increasing interest in complementary and integrative approaches, including homoeopathy. This review evaluates the pathophysiology, clinical features, and standard management of knee OA and critically examines the role of homoeopathic treatment based on available clinical studies, observational research, systematic reviews, and classical homoeopathic literature. Evidence from randomized controlled trials (RCTs), feasibility trials, observational studies, and institutional reports suggests that individualised homoeopathy, as well as specific remedies such as Rhus Toxicodendron, may reduce pain, improve joint function, and enhance activities of daily living. However, the findings are limited by sample size, heterogeneity in methodology, and the need for larger, well-designed RCTs. This review highlights current evidence, strengths, limitations, and future research priorities for integrating homoeopathy into comprehensive OA management.
Keywords: Knee; osteoarthritis; chronic; degenerative